Determinants of Financial Performance of Regional Government Revenue Growth in Central Java Province, Indonesia - ., Asrori; Nur Hasanah, Juliatun; Ihlashul ‘Amal, Muhammad (KnE Social Sciences, 2020)
This study aims to examine the effect of operating performance and autonomy on the financial performance of local government with budget effectiveness as an intervening variable. The ratio of local government revenue growth is used as a proxy for the financial performance of local government. The unit of analysis of this study includes the financial statements of 29 regency governments and 6 city governments in Central Java Province, Indonesia, for three periods from 2015 to 2017. The results of this study indicate that operating performance and autonomy have a positive effect on the financial performance of a local government. This study provides empirical support for the implementation of the new public management theory to improve the financial performance of local governments, especially in increasing local own-source revenues. However, the results show that budget effectiveness is not able to mediate an increase in the influence of operating performance and autonomy on the financial performance of the growth of local government revenues. Keywords: Regional government revenue growth, autonomy, operating performance, budget effectiveness.